Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3348/kjr.2020.0191
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Abnormalities: What Radiologists Should Know

Abstract: Interstitial lung abnormalities (ILAs) are radiologic abnormalities found incidentally on chest CT that are potentially related to interstitial lung diseases. Several articles have reported that ILAs are associated with increased mortality, and they can show radiologic progression. With the increased recognition of ILAs on CT, the role of radiologists in reporting them is critical. This review aims to discuss the clinical significance and radiologic characteristics of ILAs to facilitate and enhance their manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
(85 reference statements)
0
7
0
2
Order By: Relevance
“…Additionally, it has been reported that ILAs are associated with fibrosis on pathologic correlation. Generally, ILAs are correlated with various interstitial pathologic conditions, including benign interstitial abnormalities, smoking-related interstitial fibrosis, and early-stage idiopathic pulmonary fibrosis [ 23 ]. Miller et al [ 24 ] reported that subpleural ILAs especially show a significant correlation with subpleural fibrosis and other usual findings related to interstitial pneumonia on histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that ILAs are associated with fibrosis on pathologic correlation. Generally, ILAs are correlated with various interstitial pathologic conditions, including benign interstitial abnormalities, smoking-related interstitial fibrosis, and early-stage idiopathic pulmonary fibrosis [ 23 ]. Miller et al [ 24 ] reported that subpleural ILAs especially show a significant correlation with subpleural fibrosis and other usual findings related to interstitial pneumonia on histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Copley et al demonstrated that a basal subpleural reticular pattern not associated with traction bronchiectasis on CT is frequently seen in asymptomatic elderly patients as a normal aging-related finding, independently of the smoking history. In this context, performing a correct differential diagnosis with clinically relevant interstitial lung diseases or interstitial lung abnormalities (ILA) could be particularly challenging [ 3 , 25 ].…”
Section: Main Textmentioning
confidence: 99%
“…간질성폐이상(interstitial lung abnormality; 이하 ILA)은 임상적으로 이전에 간질폐질환(interstitial lung disease; 이하 ILD)이 진단되거나 의심된 적이 없는 환자의 CT 검사에서 우연히 발견된 이상 소견이다(radiological definition based on the incidental identification of CT abnormality)( 36 37 ). 최근 폐암검진 흉부 CT와 기타 다른 진단적 목적의 다양한 CT 검사가 매우 증가함에 따라 간질성폐이상 소견에 대한 보고 또한 증가되었다.…”
Section: 간질성폐이상(Interstitial Lung Abnormality)unclassified
“…간질성폐이상과 감별이 필요하거나, 오인될 수 있는 CT 소견은 다음과 같다( 36 37 ). 중력의존무기폐(dependent lung atelectasis)가 대표적으로, 앙와위 자세에서 촬영한 CT 영상에서 중력의존 부위에 보이는 증가 음영으로 주로 양쪽 폐 하엽 후기저분절(posterobasal segments of lower lobes)에서 보인다.…”
Section: 간질성폐이상(Interstitial Lung Abnormality)unclassified